2018
DOI: 10.3892/etm.2018.5866
|View full text |Cite
|
Sign up to set email alerts
|

High calcium diet alleviates 5/6 nephrectomy-induced bone deteriorations of lumbar vertebrae in mice

Abstract: Abstract. Dietary calcium (Ca) supplementation has beneficial effects on bone health. However, it is not clear whether a high calcium diet (HCD) following 5/6 nephrectomy (5/6 Nx) is beneficial to bone health. The aim of the present study was to examine the effects of an HCD on bone metabolism using a chronic kidney disease (CKD) mouse model. Male C57BL/6J mice were divided into three groups: Sham group, 5/6 Nx group and 5/6 Nx + HCD group. Mice were sacrificed 12 weeks post-surgery. Calcium (Ca) and creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…OPG and RANKL as the mainly regulators affect the activity of osteoclast. OPG as a competitive inhibitor to RANKL blocks RANKL binding to the RANK receptor on osteoclast cells, subsequently inhibiting bone resorption and osteoclastogenesis [13]. Previous study found that the ratio of RANKL to OPG is increased in ovariectomized rats, while attenuation of the RANKL/ OPG ratio can reduce bone loss [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OPG and RANKL as the mainly regulators affect the activity of osteoclast. OPG as a competitive inhibitor to RANKL blocks RANKL binding to the RANK receptor on osteoclast cells, subsequently inhibiting bone resorption and osteoclastogenesis [13]. Previous study found that the ratio of RANKL to OPG is increased in ovariectomized rats, while attenuation of the RANKL/ OPG ratio can reduce bone loss [29].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous PTH administration leads to the catabolism of bone, while intermittent PTH administration promotes anabolic effects on bone [10,11]. Numerous studies have validated that serum PTH level is up-regulated in a variety of animal models of osteoporosis, such as ovariectomized [12] and 5/6 nephrectomy [13]. A clinical investigation indicates that post-menopausal women have higher serum PTH and lower bone density of spine and femoral neck than premenopausal women, suggesting that elevated in intact PTH is related to age, but there is no evidence to validate that PTH is a mediator of age-related bone loss [14].…”
Section: Doxercalciferol Alleviates Bone Deteriorations and Cartilagementioning
confidence: 99%
“…CKD degree was progressively increasing over time, mainly in genetic models of CKD. Surgical models were the most frequently used [ 19 , 20 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], as they offered the possibility to compare the phenotype before and after surgery and were described as stable over time. Subtotal nephrectomy, so-called 5/6th nephrectomy, mimics quite well the process of reduction in nephron mass occurring in humans during renal failure.…”
Section: Mouse Models Of Ckd–mbdmentioning
confidence: 99%
“…Thus, CKD-induced bone loss was caused by a combination of decreased osteoblast activity and enhanced osteoclast function, and the latter event appeared to be mediated by increased osteoblastic RANKL production. 78,79 Suppression of RANKL in the diosmin-treated CKD rats likely contributed to the inhibition of resorption reflected by the restoration of TRAcP-5b and osteoclast number and activity to the control levels.…”
Section: Papermentioning
confidence: 99%